Studies on management system and identification of the causes of genetic erosion of indigenous cattle in Mymensingh district - Rahman, MM; Hoque, MA; Saha, NG; Faruque, MO (Bangladesh Journal of Animal Science, 2013)
The study was conducted at four villages of Sadar Upazila of Mymensingh district to study the management system and identify the probable causes of genetic draw off of indigenous cattle. The data were collected through personal interview of 151 randomly selected farmers by using a pre-tested structured interview schedule during the period from January to April, 2012. It was observed that the cattle per household was 2.98 in number. Among the farmers, 48% of them provided soft (soiled floor with bamboo fence), 48% semi-concrete (concrete floor with half of concrete wall and half of bamboo fence), 3% of concrete house (concrete floor and wall) and other 1% had no house for their cattle. About 80%, 17% and 3% farmers reared cattle by semi-intensive, intensive and extensive or free grazing system, respectively. More than 84% of the farmers managed feed from both sources (own and purchase) for their cattle even though 15% fully depended on purchasing feed from local market, but a little (1%) of them from their own sources. Among the cow genotypes, more than half (61.16%) was of the indigenous which was significantly (p<0.01) higher than the crossbreds (38.84%). It was observed that semen of Holstein were used significantly (p<0.05) higher than that of the semen of local or any other crossbred bulls. Most of the farmers (76%) inseminated their cows artificially rather than naturally (19%) and merely of 5% did both. A small number of farmers (11%) followed the existing breeding policy while maximum of them (86%) ignored or overlooked it. The main cause of genetic erosion of indigenous cattle in the study areas, might be due to lack of adherance to breeding policy and practice of insiariminate crosses with exotoc breeds. Nevertheless, lack of farmers awareness, changes in cattle management system along with agricultural practices might have also contributed to this issue as well. It needs to develop sustainable guidelines by the relevant authorities for proper breeding practices to minimize the uncontrolled and misdirected crossing between exotic and local cattle for conserving and protecting the valuable indigenous cattle in the region. DOI: http://dx.doi.org/10.3329/bjas.v42i1.15769 Bang. J. Anim. Sci. 2013. 42 (1): 23-28